Rethinking modern prostheses in Anglo-American Commodity cultures, 1820-1939 - Jones, Claire L. (Disability History MUP., 2017)
A collection of essays examining the development and commodification of prostheses in Britain and America that occurred during the nineteenth and twentieth centuries, due to the shift to standardized industrial manufacturing and associated market growth.